Effect of high-intensity childhood games on heart rate variability, saliva leptin concentrations, and body composition in children - C.Y. Rodriguez-Triviño; S. Quintana; C.E. Osorio-Vélez; M. Garcia-Florez (Brazilian Journal of Medical and Biological Research)
The aim of this study was to evaluate the effect of high-intensity childhood games on cardiac autonomic regulation, obesity biomarkers, and body composition in overweight or obese children compared to moderate-intensity games. A single-blind, randomized controlled study was conducted including children aged 6 to 9 years with overweight or obesity. Participants were randomly assigned to two groups: 33 in the moderate-intensity interval game group (MIIG) and 29 in the high-intensity interval game group (HIIG). The intervention lasted 16 weeks, with measurements conducted under double blinding. The study followed institutional ethical standards and was registered on ClinicalTrials.gov (CT NCT05294601). A total of 74 children were recruited, with 7 excluded after sports medicine assessment, leaving 67 children randomized. Five participants dropped out during the study. HRV analysis revealed significant differences in frequency dominance in the HIIG group. High-frequency power, linked to parasympathetic dominance, increased from 59.3 to 65.8 nu (P=0.03), while low-frequency power, related to sympathetic activity, decreased from 40.6 to 34.13 nu (P=0.04). Salivary leptin concentrations decreased significantly from 0.33 to 0.32 ng/mL (P=0.008) in the MIIG group and from 0.35 to 0.32 ng/mL (P=0.004) in the HIIG group. Childhood games positively impacted anthropometry, HRV, and leptin concentrations in both intensity groups, indicating metabolic improvement. However, only the high-intensity strategy enhanced parasympathetic dominance and sympathetic-parasympathetic balance, potentially reducing long-term cardiovascular risk.